Blood flow restriction training on physical parameters in elite male canoe athletes - Ugur Tosun, Burcin; Angin, Ender; Kirmizigil, Berkiye; Yolcu, Mustafa (Lippincott Williams & Wilkins, 2023)
Background:To investigate the effect blood flow restriction (BFR) exercises on muscle size, strength and athletic performance in elite canoe athletes aged 18 to 25 years. Methods:This was a randomized controlled trial. The participants were divided into 2 groups: the intervention group (INT-gr) (n = 17, age: 18.59 +/- 0.71 years) and the control group (CONT-gr) (n = 16, age: 18.81 +/- 1.11 years). Anthropometric measurements, muscle size measured by ultrasound (US), strength measurements with an isokinetic dynamometer, and ergometer performance with an indoor ergometer were conducted before and after the exercise program. Knee flexion and extension and leg press one-repetition maximum (1 RM) tests were performed to determine the participants' training program. The INT-gr performed 1 RM 30% resistance training + BFR for 8 weeks, while the CONT-gr performed 1 RM 30% resistance training (RT) without BFR with their routine training program. US was used to measure the cross sectional area (CSA) and thickness of the quadriceps femoris (QF) and Hamstring (H) muscles in the pre-post design, and the isokinetic dynamometer was used to measure the strength of bilateral 60(degrees)/s and 300(degrees)/s peak torque (PT) values of the QF and H. Sports performance was tested on an indoor ergometer at distances of 200, 500, and 1000 m. Results:The changes in bilateral rectus femoris (RF) CSA and VL thickness measurements in the INT-gr were significant (P < .05). Ergometer performance measurements showed a significant improvement over CONT-gr at all distances (P < .05). In terms of strength scores measured by the isokinetic dynamometer, the right QF and H 300(degrees)/s and the left QF 60(degrees)/s PT values were significantly in favor of INT-gr. Conclusion:BFR exercises are effective to increase strength, muscle size, and ergometer performance in elite canoe athletes.
Keywords: BFR; canoeing; ergometer; isokinetic strength; muscle thickness